Physico-Chemical and Sensory Evaluation of Chicken Nuggets with Cooked Unripe Plantain - Selvakumar, K; Anandh, M Anna; Rajarajan, G; Ilavarasan , R; Sangeetha, A (Journal of Meat Science, 2024)
Chicken nuggets were prepared with 5%, 10%, and 15% steam cooked  unripe plantain without peel, and their qualities were evaluated. Linear  and significantly (P < 0.01) increased values were observed for emulsion  stability, cooking yield, moisture retention, fat retention, moisture, and  total ash contents. Conversely significantly (P
Keywords: Acceptability; Banana; Chicken; Fiber; Functional; Meat; Nuggets; Quality; Plantain